Pyoderma gangrenosum: update and guidance - Luiz Felipe Duarte Fernandes Vieira; Carlos Lacerda Andrade Almeida; Alexandre Wagner de Souza; Jozelia Rêgo; Everton Siviero do Vale; Jose Roberto Pereira Pegas (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The pyoderma gangrenosum (PG) is a neutrophilic disease, rare but with a poor outcome. The Capitulum of Wound treatment of the Brazilian Society of Plastic Surgery (SBCP) promoted a discussion with the Brazilian societies of Dermatology and Rheumatology to extract the best procedures in diagnostic and treatment. Methods: Broad review of published articles related to the subject and compilation of guidelines of diagnostic and treatment by two advisors of each involved society, plastic surgery, dermatology and rheumatology. Results: The PG is not an exclusion disease anymore, with well defined criteria for its diagnostic and literature based treatment, refined by the authors, including the use of biological therapies. Conclusion: The PG remains challenging, but systematizing the investigation and the use of new drugs has opened a new horizon of treatments, interfering in the pathophysiology in a positive manner with fewer side effects than immunosuppressive therapy alone.